PERSEPSI MASYARAKAT TENTANG CITRA HOTEL MELATI DI KECAMATAN KOTO TANGAH KOTA PADANG - Yandra, Yandra; Yuliana, Yuliana; Pramudia, Heru (Journal of Home Economics and Tourism, 2015)
This study aimed to describe the public perception of the image of budget hotels in the District Tangah Koto Padang. This type of research is quantitative descriptive. The study population was people who were around the budget hotels in the city of Padang District of Koto Tangah amounted to 275 people. The sampling technique in this research is non probability sampling using purposive sampling. The number of samples in this study 74 people. Data collection techniques performed using a questionnaire using a Likert scale that has been tested for validity and reliability. Results of research describing About Public Perception image Bed in District Tangah Koto Padang. otherwise the unfavorable category with an average value of 60.20 in the range of 49-> 63. While each of the indicators are: (1) The impression otherwise unfavorable category with an average value of 15.716, in the range of 18 -> 24 (2) Belief expressed unfavorable category with an average value of 26.31, in the range of 21- < 27. (3) The attitude expressed unfavorable category with an average value of 18.17, in the range 15,75- <20.25. Keywords: Perception, Society, Citra other star hotel1 Prodi